Electrochemical synthesis of polymer microgels1. Issue 21 (7th June 2015) - Yan, Suting; Wu, Qingshi; Chang, Aiping; Lu, Fan; Xu, Hai-Chao; Wu, Weitai
<x xml:space="preserve">Abstract</x> Electrochemistry is used in the synthesis of polymer microgels through polymerization of the monomer in the presence of the crosslinker.